Navigating the Paradox of FOMO and Faith: A Multidimensional Clustering of Women’s Financial Management Behavior - Kartika Ayu Kinanti; Yulian Ade Chandra; Firdaus Al Maidah; Ananda Salsabila Kenyo Sarasati; Dea Rahayu (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This research offers a novel integration of psychological drivers (FOMO) and sociocultural values (religiosity) within a multidimensional clustering framework to analyze women’s financial behavior in the Tapal Kuda region. By employing the Fuzzy Possibilistic C-Means (FPCM) algorithm, this study maps the heterogeneity of financial conduct across variables of age, literacy, and consumption patterns. Analyzing survey data from 384 respondents, the FPCM approach successfully identified four distinct behavioral archetypes: Good, Moderate, Poor, and Extreme Consumption. Empirical findings reveal a significant generational divide: women aged 25–34 exhibit the highest financial resilience, while the 18–24 cohort remains the most vulnerable within the ‘Poor’ cluster. Paradoxically, the 45–54 age group shows a high propensity for ‘Extreme Consumption’ where modern psychological pressures (FOMO) frequently override religious discipline. Technical analysis further confirms that excluding age as a clustering variable produces a more robust and balanced distribution. These results provide a foundation for specialized financial inclusion programs that must shift beyond basic literacy to include psychological mitigation of FOMO, ensuring long-term financial stability tailored to specific demographic profiles.